STRATEGI DALAM MENCETAK GURU DALAM ERA DIGITAL - Edy Riyanto (Pendidikan Seni Pertunjukan Fakultas Keguruan dan Ilmu Pendidikan Universitas Sultan Ageng, 2023)
There are three kinds of intelligence that humans have. The first is intellectual intelligence, which is an intelligence that provides the ability to count, analogize, imagine, and have the power of creation and innovation. The second is emotional intelligence includes self-control, enthusiasm, and perseverance, as well as the ability to motivate yourself and survive the frustration, the ability to control impulses and emotions, not excessive in pleasure, regulate mood and keep the burden of stress does not paralyze the ability to think , to read other people's deepest feelings (empathy) and pray, to maintain the best possible relationship, the ability to resolve conflicts, and to lead oneself and the surrounding environment. Furthermore, spiritual intelligence is the intelligence to deal with problems of meaning or value to place our behavior and life in the context of a broader and richer meaning. Future teachers are teachers who have intellectual abilities, emotional and spiritual abilities and have skills that can create optimal learning outcomes, have sensitivity in reading the signs of the times, have intellectual insight and forward thinking, and have never been satisfied with knowledge available to him if the three intelligences above we can have, and implemented as a professional teacherKeywords: Teacher, Professional, Intellectual Intelligence, emotional